(untitled) (Orthodontic Journal of Nepal, 2020)
Introduction: Maxillary lateral incisor is a common congenitally missing tooth in the oral cavity. Maxillary lateral incisor is also the most common varying tooth in form than any other tooth. The objective of the study is to estimate the prevalence of congenitally missing maxillary lateral incisors and peg laterals in patients receiving orthodontic treatment. Materials & Method: This is a cross sectional retrospective study carried out among 204 orthodontic patients. Panoramic radiographs taken during the diagnostic procedure of orthodontic treatment was used to confirm the presence or absence of lateral incisors. The presence of peg laterals was determined by dental casts. Result: Prevalence of missing maxillary lateral incisors and peg laterals was found 2.5% and 3.9% respectively. Prevalence of missing lateral in male was 5.7% while among female no missing laterals were observed. Prevalence of peg laterals in male and female was 1.1% and 6% respectively. Among the missing lateral incisors, prevalence of bilaterally missing lateral incisors was 60% while prevalence of both right and left unilateral missing laterals was 20%. Among the peg laterals, bilateral peg laterals were present in 50% patients, followed by left unilateral 37.5% and right unilateral 12.5% peg laterals. Conclusion: The present study shows higher prevalence of peg laterals than missing lateral incisors. Prevalence of missing lateral incisors was higher in male and prevalence of peg laterals was higher in female. Prevalence of bilaterally missing laterals and bilateral peg laterals was higher than unilateral presentation.